Meninjau Ulang "Sepakat": Menelaah Kelayakan Konsep Sepakat dalam Perjanjian Platform Digital berdasarkan Kitab Undang-Undang Hukum Perdata Indonesia - Adis Nur Hayati (Jurnal HAM, 2025)
Consent is often considered a concrete representation of an individual's will to freely choose independently. It is associated with the concept of individual autonomy, which is underpinned by the right to make one's own choices and freedom from coercion. However, in practice, consent within standard agreements on digital platforms often fails to reflect a truly voluntary and informed consumer agreement. Consumers' provision of consent on digital platforms frequently occurs without adequate understanding, genuine choice, or real bargaining power due to manipulation and undue influence exerted through dark patterns employed by platform operators. Therefore, this paper aims to analyze the adequacy of the concept of consent in the Indonesian Civil Code when applied to digital platform transactions. It employs a doctrinal legal research method to analyze the relevant provisions and their practical implications in the digital context. This paper argues that the current concept of consent in the Indonesian Civil Code is no longer adequate for application in digital platform environments. In particular, the act of providing consent through mechanisms such as an "I agree" checkbox and other similar formats may not genuinely reflect the consumer's informed and voluntary consent.